Abstract 15325: Dynamic Change From Mitochondrial Compensation to Mitochondrial Failure During Aortic Disease Progression and Dissection Formation - Li, Yanming; Zhou, Zhen; Zhang, Chen; Vasquez, Hernan; Li, Yang; Chakraborty, Abhijit; Rebello, Kimberly; Zhang, Lin; Ren, Pingping; Azares, Alon R; Chen, Rui; li, yumei; et al. (Circulation (New York, N.Y.), 2022)
IntroductionAscending thoracic aortic aneurysm (ATAA) progression to dissection (ATAD) is associated with a high risk of mortality. Since the specific molecular and cellular changes leading to dissection are poorly understood, we compared transcriptome profiles of aortic smooth muscle cells (SMCs) between ATAD, ATAA, and controls. MethodsWe performed single-cell RNA sequencing (scRNA-seq) of ascending aorta tissues from patients with acute ATAD (dissected and non-dissected areas were collected separately, 3 women, 5 men) and ATAA without dissection (3 women, 4 men), and from control subjects without aortic diseases (transplant donors, 3 women, 5 men). SMCs clusters were analyzed and immunofluorescence staining was performed to confirm expression of key genes. Mice exposed to β-aminopropionitrile monofumarate (BAPN) starting at P21 were used to investigate the changes of mitochondria-related genes during disease progression in undissected mice. ResultsCompared with controls, SMCs in ATAA exhibited an adaptive response characterized by upregulation of a subset of focal adhesion and contractile genes and a pro-fibroblast phenotype. These expression changes were decreased in SMCs in ATAD, which instead exhibited significant increases in genes for inflammatory response, glycolysis, senescence and cell death. Additionally, mitochondrial genes including tricarboxylic acid (TCA) cycle genes (e.g. SDHB, FH, and MDH2) and mitochondria genome genes (e.g. MT-ND4, MT-CO2, and MT-CYB), exhibited increased expression in ATAAs, and downregulated in ATADs. Immunofluorescence staining of corresponding proteins confirmed some key findings. Consistent with human data, scRNA-seq showed increased mitochondria-related genes in SMCs in BAPN mouse model at P35 when aneurysms form, which were decreased in the proximal aortic tissues after the onset of dissection deaths in surviving mice at P42. ConclusionsOur data suggest a dynamic change from mitochondrial compensation to failure with progression from normal to aortic aneurysms to dissections, which ultimately increases cell death pathways.